Dual RNA Sequencing Reveals Key Events When Different Giardia Life Cycle Stages Interact With Human Intestinal Epithelial Cells In Vitro - Rojas, Laura; Grüttner, Jana; Ma’ayeh, Showgy; Xu, Feifei; Svärd, Staffan G. (Frontiers in Cellular and Infection Microbiology, 2022)
Giardia intestinalis is a protozoan parasite causing diarrheal disease, giardiasis, after extracellular infection of humans and other mammals’ intestinal epithelial cells (IECs) of the upper small intestine. The parasite has two main life cycle stages: replicative trophozoites and transmissive cysts. Differentiating parasites (encysting cells) and trophozoites have recently been shown to be present in the same regions of the upper small intestine, whereas most mature cysts are found further down in the intestinal system. To learn more about host-parasite interactions during Giardia infections, we used an in vitro model of the parasite’s interaction with host IECs (differentiated Caco-2 cells) and Giardia WB trophozoites, early encysting cells (7 h), and cysts. Dual RNA sequencing (Dual RNAseq) was used to identify differentially expressed genes (DEGs) in both Giardia and the IECs, which might relate to establishing infection and disease induction. In the human cells, the largest gene expression changes were found in immune and MAPK signaling, transcriptional regulation, apoptosis, cholesterol metabolism and oxidative stress. The different life cycle stages of Giardia induced a core of similar DEGs but at different levels and there are many life cycle stage-specific DEGs. The metabolic protein PCK1, the transcription factors HES7, HEY1 and JUN, the peptide hormone CCK and the mucins MUC2 and MUC5A are up-regulated in the IECs by trophozoites but not cysts. Cysts specifically induce the chemokines CCL4L2, CCL5 and CXCL5, the signaling protein TRKA and the anti-bacterial protein WFDC12. The parasite, in turn, up-regulated a large number of hypothetical genes, high cysteine membrane proteins (HCMPs) and oxidative stress response genes. Early encysting cells have unique DEGs compared to trophozoites (e.g. several uniquely up-regulated HCMPs) and interaction of these cells with IECs affected the encystation process. Our data show that different life cycle stages of Giardia induce different gene expression responses in the host cells and that the IECs in turn differentially affect the gene expression in trophozoites and early encysting cells. This life cycle stage-specific host-parasite cross-talk is an important aspect to consider during further studies of Giardia’s molecular pathogenesis.